Analisis Kelimpahan Mikroplastik pada Air Permukaan dan Biota di Sungai Air Hitam Kota Pekanbaru, Riau - Darmayanti, Lita; Priyambada, Gunadi; Khairani , Ayu Dhea (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2025)
Microplastics are plastic particles with a size of 1 μm – 5 mm that are widely present in surface water and sediments. Increased exposure to microplastics in water can affect food chain cycles, leading to bioaccumulation and biomagnification in fish. This study aims to analyze the abundance, types, and polymer types of microplastics in surface water and fish in the Air Hitam River, Pekanbaru City, Riau. Air Hitam River is one of the tributaries of Siak River which has a length of ±8,5 km. Determination of sampling locations for each segment using purposive sampling method based on existing conditions along the river flow by identifying sources of microplastic pollution. The results showed that the average abundance of microplastics in the waters of Air Hitam River was 330±150,3 particles/L. The average abundance of microplastics in 8 Chitala lopis was 0,86±0,24 particles/gram for meat samples and 4,35±0,4 particles/gram for gill and digestive tract samples. The types of microplastics found in this study are fragments, fibers, films, and pellets. The results of the Pearson Product Moment correlation analysis showed that there was a significant relationship between aquatic environmental parameters (temperature, pH, and flow velocity) and the abundance of microplastics in the Air Hitam River with a sig value. (0,005 < α 0,05) for temperature parameter, sig. (0,215 > α 0,05) for the pH parameter, and sig. (0,248 > α 0,05) for the flow velocity parameter. The polymer types identified based on the Differential Scanning Calorimetry (DSC) test results are Polycarbonate (PC) and Polypropylene (PP).